2011
DOI: 10.1016/j.rmed.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Topical nasal steroid treatment does not improve CPAP compliance in unselected patients with OSAS

Abstract: Fluticasone propionate as a nasal topical steroid does not reduce CPAP-induced unwanted nasal side effects, and has no beneficial effect on CPAP compliance during the first four weeks of treatment in unselected patients with OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…In unselected patients, there is little evidence that nasal corticosteroids improve CPAP tolerability. In a study by Strobel and coworkers, twice daily fluticasone used for 10 days prior to and 4 weeks following the initiation of CPAP provided no improvement in nasal symptoms, nasal peak flow values, or CPAP use [36]. Similarly, Ryan and colleagues found that humidification, but not fluticasone, decreased the frequency of nasal symptoms in patients on CPAP.…”
Section: Chronic Rhinitismentioning
confidence: 98%
“…In unselected patients, there is little evidence that nasal corticosteroids improve CPAP tolerability. In a study by Strobel and coworkers, twice daily fluticasone used for 10 days prior to and 4 weeks following the initiation of CPAP provided no improvement in nasal symptoms, nasal peak flow values, or CPAP use [36]. Similarly, Ryan and colleagues found that humidification, but not fluticasone, decreased the frequency of nasal symptoms in patients on CPAP.…”
Section: Chronic Rhinitismentioning
confidence: 98%
“…En nuestra población, aunque el 100% de los pacientes reportaron que utilizaron humidificador, no se identificó un impacto positivo en los pacientes con rinitis ni en la adherencia al CPAP. Asimismo, los estudios realizados con corticoides inhalados han demostrado una mejoría en los síntomas nasales durante el tratamiento, se ha observado un efecto de rebote con la suspensión o únicamente se han identificado que puede beneficiar pacientes particulares con SAHOS (17,18). Nuestros resultados demuestran que el uso de corticoides inhalados impactan en la adherencia terapéutica al CPAP, sin embargo, esto puede constituir un surrogado de la presencia de rinitis, dado que el mismo número de pacientes que presentaron rinitis también reportaron uso de corticoides inhalados.…”
Section: Características (N=56) Frecuencia N (%) Media (De) Mediana (unclassified
“…Heated humidification seems to increase adherence, perhaps by reducing nasopharyngeal side effects [31], although treatment of rhinitis with nasal steroids does not increase PAP therapy adherence in an unselected patient population [32,33]. Patient input on interface selection and fitting is needed to reduce leakage, minimize abrasion, and increase comfort.…”
Section: Establishing Treatmentmentioning
confidence: 99%